Possible Traffic Safety Effects of the Implementation of Section Control in Hungary - Sándor, Zsolt (Acta Technica Jaurinensis, 2020)
This article presents the anticipated safety effects of the implantation of section control in Hungary. The proposed results were originated from international studies and the local circumstances. Effects are depending on the control coverage and the magnitude of the sanctions. Direct (short term benefits) and indirect effects (long term benefits) can be identified. Direct effects are the decreasing of accident numbers, while indirect effects are the decrease of other externalities of transport like environmental loads. Based on the results the implementation cost of the enforcement system is measureable with the proposed social cost savings come from the decreasing number of accidents.